Primary sclerosing cholangitis: what is new in the therapeutic landscape - Curto, Armando; Cristoferi, Laura; Carbone, Marco; Galli, Andrea; Invernizzi, Pietro (Current opinion in immunology, 2025)
Primary sclerosing cholangitis (PSC) is a rare, chronic cholestatic liver disease affecting the intra- and extra-hepatic bile ducts, leading to progressive inflammation and fibrosis. Its pathogenesis is complex and involves genetic predisposition, environmental triggers, and their interaction through the gut–liver axis, mediated by the microbiota. To date, no approved therapies modify the natural history of PSC, and liver transplantation remains the only curative option. This review provides an overview of current investigational therapies for PSC, emphasizing their mechanisms of action and relevance to the underlying disease biology. It also examines key challenges in therapeutic development, including the lack of validated surrogate end points, clinical heterogeneity, and the confounding effects of concomitant inflammatory bowel disease treatments factors that complicate trial design and interpretation. Clarifying these aspects is essential to support the development of effective, targeted therapies for this complex and currently untreatable condition.